2020
DOI: 10.3390/md18030166
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholines and Chlorophyll-Derived Molecules from the Diatom Cylindrotheca closterium with Anti-Inflammatory Activity

Abstract: Microalgae have been shown to be excellent producers of lipids, pigments, carbohydrates, and a plethora of secondary metabolites with possible applications in the pharmacological, nutraceutical, and cosmeceutical sectors. Recently, various microalgal raw extracts have been found to have anti-inflammatory properties. In this study, we performed the fractionation of raw extracts of the diatom Cylindrotheca closterium, previously shown to have anti-inflammatory properties, obtaining five fractions. Fractions C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 57 publications
1
40
0
2
Order By: Relevance
“…This review also reports other important bioactivities shown for PPBa, such as antiviral [43], anti-inflammatory [6,[45][46][47], antioxidant [48][49][50][51], immunostimulatory [53] and anti-parasite activities [56]. These data show how this compound can have a plethora of applications for different human pathologies.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…This review also reports other important bioactivities shown for PPBa, such as antiviral [43], anti-inflammatory [6,[45][46][47], antioxidant [48][49][50][51], immunostimulatory [53] and anti-parasite activities [56]. These data show how this compound can have a plethora of applications for different human pathologies.…”
Section: Resultsmentioning
confidence: 81%
“…In recent years, many studies have investigated possible microalgae anti-inflammatory properties [6,45,46]. A recent study by Lauritano et al [47] investigated the capacity of extracts of the diatom Cylindrotheca closterium to inhibit the release of one of the main effectors of inflammation, Tumor Necrosis Factor α, in Lipopolysaccharide-stimulated human THP-1 monocytic leukemia cells (ATCC®TIB-202 TM ). They tested five fractions and identified Fraction C as the most active, able to inhibit 60% of Tumor Necrosis Factor α release at 100 µg/mL and 40% of Tumor Necrosis Factor α release at 50 µg/mL concentration.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Microalgae are photosynthetic organisms adapted to live in several different environments, including marine, freshwater, polar, temperate and tropical. They are also known to produce a plethora of metabolites derived from primary and secondary metabolism, which have shown possible applications for human health (e.g., compounds with anti-cancer, anti-microbial, anti-diabetes, anti-epilepsy, anti-inflammatory, anti-atherosclerosis, anti-osteoporosis, immunomodulatory and antioxidant activities; [1][2][3][4][5][6][7][8][9][10]). Various studies have focused on the discovery of metabolic pathways involved in the synthesis of bioactive compounds [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The LCMS analysis indicated the presence of various metabolites with antimicrobial, anti-inflammatory and antiparasitic potential [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Though there is a lack of information regarding the antiparasitic potential of these metabolites against marine parasites, their effectiveness against other parasites were widely reported [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Some of the important metabolites are phytosphingosine ( 6 ), a naturally occurring lipid which acts as antimicrobial (gram-positive bacteria, yeast and moulds) and anti-inflammatory [ 29 ].…”
Section: Discussionmentioning
confidence: 99%